Effect of planting density and abiotic conditions on yield of Betula pendula and Pinus sylvestris seedlings in monoculture and mixture - McGuinness, Jennifer (2014)
How the yield of mature stands changes in response to factors such as stand composition, planting density and abiotic conditions is a developing topic, and underpins models and generalizations used by forest managers today. However, these generalizations are both the subject of debate and are limited to mature stands, leaving a knowledge gap concerning both mixed species stands and younger stands. I performed this study to address this knowledge gap. Using seedlings of two common boreal tree species (Betula pendula Roth and Pinus sylvestris L.), three planting compositions (two monocultures and one 50:50 mixture), four planting densities (2, 8, 16 and 24 seedlings per pot) and four abiotic condi-tions (high nutrient + high water, high nutrient + low water, low nutrient + high water and low nutrient + low water) I tested the effects of these factors on the yield characteristics of seedlings. Under greenhouse conditions seedlings were grown for 10 weeks in a full factorial block design experiment. Total seedling masses, mean seedling masses, above and below ground (A:B) masses, A:B ratio, mortality, height and diameter were measured to observe if changes in seedling yield characteristics occurred. My results show that seedling yield is affected by all three factors; species composition, density and abiotic environment, as well as interactions among them. The significant interaction terms indicated not only that the seedling performance differed among planting compositions (e.g. between seedling mono-cultures and mixtures), but that the effects were also dependent on both the planting density and the abiotic conditions. Total mass, above ground mass and below ground mass of monocultures and mixed planting composition significantly increased with increased densi-ty in all planting compositions. While mean seedling mass, and seedling diameter showed significant decrease with increasing density. While often not statistically significant the change in seedling performance of each planting composition with increasing density var- ied with abiotic conditions. Under conditions of high nutrient + high water an overyielding effect is observed, notably at intermediate planting densities. However, yield in mixtures was only significantly different from birch monocultures. When mean seedling mass was plotted on a log mass - log density scale the observed relationships were all negative but varied in intensity, when planting composition and abiotic conditions were changed refut-ing the self thinning rule and proposed constant slope. The results from this experiment suggest that these three factors and their interactions influence yield in seedlings, and that overyielding may occur under specific conditions. These results also contribute to the de-bate on the general applicability of the self-thinning law, by showing that the relationship between yield and density is not constant. Such findings contribute to the understanding of yield and the effects of stand characteristics on seedling performance.